Del juez al constituyente: el tribunal de justicia y la transformación constitucional de la Unión Europea - Neves Pérez, Hugo (Pontificia Universidad Católica del Perú, 2025)
This article analyzes the process of constitutionalization of the European Union in the absence of a formal Constitution, focusing on the role of the Court of Justice of the European Union as a de facto constituent power. Through the study of both foundational and recent case law, it is demonstrated that the court has progressively built a normative order with constitutional features, based on principles such as primacy, direct effect, the autonomy of EU law, the protection of fundamental rights, and the values enshrined in Article 2 of the Treaty on European Union. The article also examines the conflicts between the Court of Justice of the European Union and various national constitutional courts (notably those of Germany, Poland, and Spain), which illustrate the tension between European legal unity and internal constitutional pluralism. Finally, it reflects on the viability of a future formal Constitution for the EU and defends the thesis that, in the absence of such a text, European constitutionalism is expressed in a functional, material, and judicially consolidated form-albeit not without challenges in terms of democratic legitimacy and institutional cohesion.

Este artículo analiza el proceso de constitucionalización de la Unión Europea en ausencia de una Constitución formal, centrándose en el papel del Tribunal de Justicia de la Unión Europea como poder constituyente de facto. A través del estudio de su jurisprudencia fundacional y reciente, se demuestra que el referido tribunal ha construido progresivamente un orden normativo con rasgos constitucionales, basado en principios como la primacía, el efecto directo, la autonomía del ordenamiento jurídico, la protección de los derechos fundamentales y los valores del artículo 2 del Tratado de la Unión Europea. Se examinan, además, los conflictos entre el Tribunal de Justicia de la Unión Europea y diversos tribunales constitucionales nacionales (Alemania, Polonia y España), que reflejan las tensiones entre la unidad jurídica europea y la pluralidad constitucional interna. Finalmente, se reflexiona sobre la viabilidad de una futura Constitución formal para la Unión y se defiende la tesis de que, mientras esta no exista, el constitucionalismo europeo se manifiesta en una forma funcional, material y judicialmente consolidada, aunque no exenta de desafíos en términos de legitimidad democrática y cohesión institucional.
From judge to constituent: the court of justice and the constitutional transformation of the European Union
Keywords: European constitutionalism; Primacy; Charter of Fundamental Rights; Article 2 TEU; European integration; Constitucionalismo europeo; Primacía; Carta de Derechos Fundamentales; Artículo 2 TUE; Integración europea; https://purl.org/pe-repo/ocde/ford#5.05.01